The Indian in the Cupboard - Oz, Frank; David, Keith; Lindsay Crouse; Litefoot; Richard Jenkins; Rishi Bhat; Steve Coogan; Hal Scardino (USA Columbia Pictures Corporation, 1995)
On his ninth birthday a boy receives many presents. Two of them first seem to be less important: an old cupboard from his brother and a little indian figure made of plastic from his best friend. But these two presents turn out to be much more magic than the rest...
On his ninth birthday a boy receives many presents. Two of them first seem to be less important: an...
Lynne Reid Banks
Languages : English, German, Hungarian, Swedish
Languages : English, German, Hungarian, Swedish Subtitles : English, Turkish, German, Arabic, Bulgarian, Dutch, Romanian
Keywords: Adventure; Fantasy; Family